Chemically functionalized cellulose nanofibrils-based gear-like triboelectric nanogenerator for energy harvesting and sensing. (December 2019) - Zhang, Chenyuan; Lin, Xuejiao; Zhang, Ni; Lu, Yanxv; Wu, Zhengmei; Liu, Guanlin; Nie, Shuangxi
Abstract: Cellulose is the most abundant natural polymer with low cost, high strength, good chemical modification property and biodegradability. In this work, a cellulose-based triboelectric material is prepared by surface amino modification and silver nanoparticle coating treatment of cellulose nanofibrils (CNFs), and a novel and simple CNF-based gear-like triboelectric nanogenerator (TENG) is designed. The three-dimensional space structure increases the frictional contact area by approximately four times compared with an ordinary planar structure. This gear-like structure shows good flexibility and integration, and the maximum open-circuit voltage can reach 286 V when three pairs of gear-like structures are assembled. The maximum power density is 0.43 W/m 2 with a load resistance of 5 × 10 7 Ω, and the resulting electrical output can directly power 60 light-emitting diodes. Moreover, TENG exhibits exceptional sensitivity and responsiveness when used as a self-powered sensor. It can reflect the change in the state of human touch through electric signals and also respond to the changes in small forces caused by water drop and vibration in the substrate. This study not only introduces a green CNF-based triboelectric material, but also presents for the first time a high-performance TENG with a gear-like structure and applies it to self-powered sensing. Graphical abstract: Image 1 Highlights: A modified CNF-based TENG with a Voc and Isc, which are 47% and 83% higher than the regular TENG, respectively. A three-dimensional gear-like structure TENG is proposed to increase the friction contact area. Multi-direction energy harvesting based on contact separation and sliding is enabled with TENG. The proposed TENG exhibits high sensitivity to touch, water drop and vibration for self-powered sensing.